Hypertension and Lifestyle Related Risk Factors (Interest : Jurnal Ilmu Kesehatan, 2026)
Background: Hypertension is a leading cause of stroke, heart failure, and chronic kidney disease, contributing to substantial morbidity, mortality, and economic burden on healthcare systems globally. This study aims to identify risk factors associated with the prevalence of hypertension among a rural community in Central Java.Methods: The study employed a cross-sectional design involving 100 respondents selected via purposive sampling. Data collection took place between July and August 2025, utilising blood pressure measurements and the completion of a questionnaire on respondent characteristics. Bivariate analysis was performed using the chi-square test, whilst multivariate analysis employed multiple logistic regression.Results: The proportion of respondents with hypertension reached 57%. Bivariate analysis demonstrated significant associations between hypertension and age (p = 0.012), BMI/obesity (p = 0.003), physical activity (p = 0.015), high-salt diet (p = 0.001), and stress level (p = 0.045), whilst smoking was not significant (p = 0.084). Multivariate analysis identified high-salt diet as the most dominant risk factor (AOR = 4.72; 95% CI: 2.11–10.56), followed by obesity (AOR = 3.80; 95% CI: 1.74–8.26) and low physical activity (AOR = 2.65; 95% CI: 1.21–5.81).Conclusion: Hypertension incidence is influenced by a combination of lifestyle and physiological factors. Integrated promotive and preventive strategies targeting salt reduction, weight management, physical activity, and stress management are required within primary healthcare services.
Keywords: hypertension; obesity; physical activity; risk factors; salt intake